Implementation Of The School Literature Movement (Slm) During The Covid-19 Pandemic In Junior High School In West Java Province, Indonesia - Hadiansah, Deni; Trisnamansyah, Sutaryat; Warta, Waska; Iriantara, Yosal (International Journal of Educational Research & Social Sciences, 2022)
The low literacy skills of students in primary and secondary schools in the Republic of Indonesia (RI), since 2015 the government has implemented the School Literacy Movement (SLM) program. It is only that in early 2020 the program was disrupted due to the COVID-19 pandemic. This research is to describe how the SLM program was implemented during the COVID-19 pandemic in a secondary school in West Java Province, Indonesia. This descriptive qualitative research uses the literature study method. The main reference sources are literacy movement manuals published by the Indonesian government, activity programs compiled by the school, and other secondary sources. The results showed that with the active collaboration of school residents, SMP ASBP KBB and SMP NKB West Java Province, Indonesia, continued to implement the SLM program even though during a pandemic emergency. Various initiatives made schools more adaptive to the presence of internet technology, making activities more meaningful, integrated, and appropriate. parameters have been able to create a Literate School Ecosystem (LSE) as the main goal of program success.